William H. Bradbury papers - Bradbury, William H., 1829-1900.
Chiefly letters (1862-1865) from Bradbury to his wife, written while serving with the 129th Illinois Infantry Volunteers in Tennessee and with Gen. William T. Sherman in Georgia. The letters relate primarily to personal, family, and financial matters. Also includes references to Bradbury's part-time work as a war correspondent for the Chicago Tribune and the Manchester Guardian.
Soldier and lawyer, of Dwight, Ill.
Collection material in English.
Keywords: Tennessee -- History -- Civil War, 1861-1865.; Georgia -- History -- Civil War, 1861-1865.; Sherman, William T. -- 1820-1891.; United States. -- Army. -- Illinois Infantry Regiment, 129th (1862-1865); Chicago tribune; Guardian (Manchester, England); American newspapers -- Illinois; English newspapers -- Manchester; United States -- History -- Civil War, 1861-1865 -- Journalists; Lawyers; Soldiers